2006
DOI: 10.1002/ejoc.200500754
|View full text |Cite
|
Sign up to set email alerts
|

A Selective and Rapid Access to Six‐ or Seven‐Membered Ring Iminosugars via 6,8‐Diazabicyclo[3.2.1]oct‐6‐ene Intermediates

Abstract: A selective and rapid access to six-or seven-membered ring iminosugars is reported. The key step of the strategy involves the highly regio-and stereoselective reduction of 6,8-diazabicyclo[3.2.1]oct-6-ene intermediates, depending on the nature of imine substituents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Therefore, it was decided to use the protected form, which was obtained by benzylation of the hydroxyl functions (Scheme 2). 26 In contrast with the CN(R,S) synthon, the treatment of 2 with LDA in the presence of iodomethane gave two different products: the desired C5-alkylated compound 3 and an α-cyanoenamine 4, in 10% and 30% yield, respectively. The major compound 4 was obtained through the elimination of the adjacent benzyloxy group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was decided to use the protected form, which was obtained by benzylation of the hydroxyl functions (Scheme 2). 26 In contrast with the CN(R,S) synthon, the treatment of 2 with LDA in the presence of iodomethane gave two different products: the desired C5-alkylated compound 3 and an α-cyanoenamine 4, in 10% and 30% yield, respectively. The major compound 4 was obtained through the elimination of the adjacent benzyloxy group.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, we decided to consider the chiral building block 1 ( Figure 1) as starting material. 25 As a part of our ongoing research program on the reactivity of compound 1, we already reported a rapid access to substituted six-or seven-membered ring iminosugars via ring-expansion reactions 26 and a new asymmetric synthesis of (2S,3R,4R,5S)-trihydroxypipecolic acid. 27 In order to prepare indolizidine analogs such as castanospermine derivatives, we have extended, herein, our research on the alkylation study at the C-5 position of the building block 1 (Scheme 1).…”
Section: Figurementioning
confidence: 99%
“…The rationale for the 3,7 trans configuration of 4a and 4e remains unclear. One notable aspect of this strategy is that it allows a fast access to 7-C-alkyl-3,4,5,6-tetrahydroxyazepanes, which have been scarcely reported, and could display potent glycosidase inhibition and a pharmacological chaperone profile . Polyhydroxylated azepanes are useful synthons for generating polysubstituted piperidines through ring isomerization .…”
mentioning
confidence: 99%